1977
DOI: 10.1111/j.1476-5381.1977.tb07542.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF ZINC ON ANAPHYLAXIS in vivo IN THE GUINEA‐PIG

Abstract: The protective effects of pretreatment with zinc sulphate aerosols against bronchoconstriction induced by egg albumen or histamine aerosols were assessed in sensitized or non-sensitized guinea-pigs respectively. Pretreatment with an adequate concentration of zinc sulphate aerosol significantly prolonged the time of onset of bronchoconstriction in sensitized guinea-pigs challenged with egg albumen, but did not appreciably alter the onset time of histamine-induced bronchoconstriction in non-sensitized animals. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1979
1979
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In a murine model of ovalbumin-induced lung allergic hypersensitivity, zinc deprivation enhanced airway inflammation and epithelial damage (16). Similarly, brief exposure to aerosolized zinc sulfate protected guinea pigs against allergic bronchoconstriction and prevented most pulmonary complications associated with this model (5). In our investigation, we observed that zinc deprivation led to a substantial increase in lung epithelial susceptibility to extrinsic apoptosis and contributed to a loss of barrier function.…”
Section: Discussionmentioning
confidence: 82%
“…In a murine model of ovalbumin-induced lung allergic hypersensitivity, zinc deprivation enhanced airway inflammation and epithelial damage (16). Similarly, brief exposure to aerosolized zinc sulfate protected guinea pigs against allergic bronchoconstriction and prevented most pulmonary complications associated with this model (5). In our investigation, we observed that zinc deprivation led to a substantial increase in lung epithelial susceptibility to extrinsic apoptosis and contributed to a loss of barrier function.…”
Section: Discussionmentioning
confidence: 82%
“…Effects on histamine release may explain the protection by Zn sulphate aerosols against OVA-induced bronchoconstriction in guinea pigs [205] as well as inhibition by Zn gluconate of IgEdependent contraction of guinea pig trachea [206]. Zn also blocks eosinophil cationic protein release from eosinophils [207].…”
Section: Functional Consequencesmentioning
confidence: 97%
“…Issues that will need to be considered are Zn dosages, type of Zn compound, route of administration and concurrent therapy. While Zn has been administered into the nasal cavity by electrolysis to treat hay fever in humans [215] and by nebulization to prevent allergen-induced bronchoconstriction in sensitized guinea pigs [205], the most practical, natural and safest route is orally. In addition, Richter and colleagues [188] have demonstrated that addition of Zn to the drinking water was effective in decreasing airway eosinophilia in mice.…”
Section: Zinc Supplementationmentioning
confidence: 99%
“…In contrast brief exposures to zinc sulphate aerosols have been shown to protect against allergic bronchoconstriction in guinea pigs, possibly by blocking histamine release from mast cells 51 . Zinc has also been shown to directly decrease the incidence of respiratory infections in young children from developing countries.…”
Section: Is Zinc Beneficial or Detrimental For Respiratory Diseases?mentioning
confidence: 99%